SCJP Exam for J2SE 5 A Concise and Comprehensive Study Guide for The Sun Certified Java Programmer Exam - Sanghera, Paul.; SpringerLink (Online service) (Berkeley, CA : Apress, 2006)
Best selling author Paul Sanghera offers cohesive, concise, yet comprehensive coverage of all the topics included in the Sun Certified Programmer for Java 5 exam (CX 310-055). With a laser sharp focus on the exam objectives, this study guide goes beyond just being an "exam cram." The material is presented in a logical learning sequence: a section builds upon previous sections and a chapter on previous chapters. All concepts, simple and complex, are defined and explained when they appear the first time. There is no hopping from topic to topic and no technical jargon without explanation. No prior knowledge of Java programming is assumed. The single most difficult aspect of this exam is to read and understand the code in the exam questions in a limited amount of time. To help you get fluent and comfortable with the code, the book offers complete runnable code examples distributed over all the chapters and a codewalk quicklet feature at the end of each chapter. Although the primary purpose of the book is to help you pass the SCJP exam, it will also serve as a good reference after the exam. Special features include: Hundreds of questions modeled after the real exam with fully explained answers. A complete practice exam with questions modeled after the real exam and fully explained answers. Hundreds of complete runnable code examples, explained in the book, that you can download and experiment with. This is a code-intensive exam. The Codewalk Quicklet feature based on the process-based codewalk philosophy to prepare you for efficient response to the code-based questions in the exam. The Exam Quick Prep feature which recaps all the important points for the last hour of preparation before taking the exam. Useful information and analysis for the programmers who are considering updating the J2SE 1.4 certification to J2SE 5.
Scratching the Surface -- Fundamentals of Java Programming -- Basic Java Programming -- Data Types and Operators -- Classes, Methods, and Interfaces -- Java Language Fundamentals -- Object-Oriented Programming -- Execution Flow Control in Java -- Advanced Java Programming -- Exceptions and Assertions -- Input and Output in Java -- Strings, Formatters, and Wrappers -- Collections and Generics -- Threads in Java.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books